2021
DOI: 10.18231/j.jchm.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

Study of neutralizing [anti-RBD] antibody responses induced by COVID-19 vaccines in healthcare professionals in a diagnostic centre of Central India

Abstract: India began administration of COVID-19 vaccines on 16 January 2021. Reliable quantification of the antibody response to SARS-CoV-2 vaccination is highly relevant for identifying possible vaccine efficiency and estimating the time of protection. Healthcare Professionals were the first group of beneficiaries of this vaccine. we aimed to evaluate the neutralizing [anti-RBD] antibody responses induced by COVID-19 vaccines after first and booster dose in healthcare professionals 69 healthcare professionals [HCPs] W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
2
Order By: Relevance
“…Although the overall seroconversion rate of 76.67% was lower than that of other studies done in India, the higher efficacy of Covishield (100% seroconversion) was true for all studies including the present study (Table 7 ) [ 26 - 28 , 39 ].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although the overall seroconversion rate of 76.67% was lower than that of other studies done in India, the higher efficacy of Covishield (100% seroconversion) was true for all studies including the present study (Table 7 ) [ 26 - 28 , 39 ].…”
Section: Discussioncontrasting
confidence: 54%
“…This was true for all other studies (Table 6) [29][30][31][32][33][34][35][36][37][38]; however, the fall in the levels of the antibodies on further assessment as reported by various studies could not be compared yet. Although the overall seroconversion rate of 76.67% was lower than that of other studies done in India, the higher efficacy of Covishield (100% seroconversion) was true for all studies including the present study (Table 7) [26][27][28]39]. This study also found a higher median level of the anti-RBD antibodies in the volunteers vaccinated with Covishield, which was similar to the findings of studies conducted by Choudhary et al [26], Patil et al [27], and Singh et al [40].…”
Section: Discussioncontrasting
confidence: 47%